The IOC s Midas Touch: Summer Olympics and City Growth - Volker Nitsch; Nicolai Wendland (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
Hosting a mega-event is a costly activity of short duration. Still, cities frequently compete to become host of all types of events. This paper examines the effect of staging the largest and most important sporting event in the world, the Summer Olympic Games, on the host city. Applying a difference-in-differences methodology, we analyze the rates of population growth of Olympic cities, candidate cities and other large cities in host and candidate countries over the period from 1860 to 2010. We find that, following the Games, host cities do not experience a measurable increase in population growth relative to cities in the control group. On the contrary, to the extent that any effect of hosting the Games is identifiable, our results indicate that being awarded the Summer Olympics has a negative impact on cities.
Keywords: R12; N90; F53; 330